Конституційно-правове регулювання права власності на землю в Україні - Озімок, І.; Ozymok, I. (Східноєвропейський національний університет імені Лесі Українки, 2019)
Конституція України досить змістовно регулює право власності на землю, визнаючи землю природним ресурсом та об’єктом права власності. Конституційними нормами регулюються окремі питання форм власності, засади реалізації права власності, захист та гарантованість права власності на землю, містяться вказівки на суб’єктів права власності на землю. Конституційне право власності на землю в Україні розглядається як право Українського народу, що підкреслює цінність та важливість зазначеного права, в порівнянні з регламентацією прав, належних людині чи громадянину.Land as an issue of property rights, is governed primarily by civil, environmental, and land laws. At the same time, the constitutional and legal regulation of land ownership is decisive for all branches of law. The Constitution of Ukraine substantially regulates land ownership by recognizing land as a natural resource and an object of property rights. In addition, the constitutional norms regulate nearly all issues of ownership, the principles of the implementation of property rights, protection and guarantee of land ownership, instructions on subjects of land ownership, as well as an obligation not to use the property to the detriment of a human and society. Such legal regulation of the constitutional right of land ownership in comparison with the constitutions of many countries of the world is more detailed, which is directly related to the importance of land for the national economy and national security. The similar legal regulation is partially observed in the constitutions of most post-Soviet states, where land occupies a prominent place in the constitutional regulation.
Constitutional and Legal Regulations of Land Ownership Rights in Ukraine
Keywords: Конституція України; право власності; право власності на землю; Constitution of Ukraine; property right; land ownership